Social-ecological resilience of communities displaced by hydroelectric dams in the Amazon:: the case of Nova Mutum Paraná, Rondônia - Simão, Berenice Perpetua; Athayde, Simone (Sustainability in Debate, 2016)
This paper presents an interdisciplinary study of processes of adaptation and cultural resilience in situations of displacement and forced relocation of social groups for hydroelectric dams in the Amazon. We present results of participatory research carried out among the Nova Mutum Paraná community in Rondônia, after forced displacement and resettlement due to the construction of the Jirau hydroelectric plant. The theoretical approach integrates concepts from theories of complex social-ecological systems with approaches from anthropology of development. Methods included participant observation, participatory workshops and focus groups, conducted for nearly three years immediately after community relocation. We analyzed social re-organization and strategies of negotiation between the community and the construction company, related to access to two spaces of cultural importance for leisure: natural bathing area and soccer field. Results suggest that the social capital existing in the community in the early stages of planning and decision making for the construction of hydroelectric projects is a critical factor for negotiating mitigation actions. The involvement and support of municipal representatives was also an important element for strengthening community social organization. Despite the obstacles and difficulties, the community persists in reconstructing their social and common living spaces, seeking to maintain their historical roots through the habits and customs practiced in the pre-displacement riverine site.